Kepadatan Campuran dengan Variasi Tumbukkan Terhadap AC-WC Gradasi Halus - Yuliansyah, Yuliansyah; Ali, Hadi; Pratomo, Priyo (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to determine the effect of variations in the compaction of thecharacteristics of the asphalt layer using the Marshall method which refers to the buildingspecifications of bina marga 2010. In the Marshall plan establishes parameters for the number ofcompaction of heavy traffic conditions compaction test specimen as 2x75 compaction with thecavity boundary mixture of 3,5- 5.5%. While on the asphalt concrete layer is studied AsphaltConcrete Wearing Coarse (AC-WC) subtle gradations lower limit.After the results of the testing materials testing both asphalt and aggregate meets the standardsand then do the manufacture asphalt mixture specimen. From the analysis of the value obtainedafter calculating the optimum asphalt content lower limit of 6,8%. Then used in mixing asphaltcontent for the variation of the collision is 2x50, 2x55, 2x60, 2x65, 2x70, 2x75, 2x80, and 2x85.After it was examined Marshall.From the test results on compaction Marshall 2x50, 2x55, 2x60, 2x65, and 2x70. Does not meetthe Marshall parameter value because Marshall Quotient (MQ) does not enter the specifications.While the value of voids In The Mix (VIM) in the collision 2x50, 2x55, 2x60, 2x65, and 2x70 arealso not included in the specification. Only on compaction of 2x75, 2x80 and 2x85 that meet theparameters of Marshall.Keywords : Compaction, Asphalt Concrete - Wearing Course (AC-WC) Subtle Gradation,Marshall Parameters, Bina Marga Specifications 2010.